Assessment of Related Factors on Delay in Diagnosis of Patients with Smear-Positive Pulmonary Tuberculosis - Salman Khazaei; Ghodratollah Roshanaei; Zahra Kousehlou; Ali Zahiri; Abdollah Mohammadian-Hafshejani; Hamid Salehiniya (مجله دانشکده پزشکی اصفهان, 2015)
Background: Approximately, one third of the world population is infected with tuberculosis (TB) germs and is put at risk of tuberculosis. Pulmonary tuberculosis accounts for more than 80 percent of cases, mostly in adults with positive sputum smear. The mortality and morbidity of the disease are associated with delay in diagnosis. Delay in diagnosis can be related to the patients or the health care system.